Wroclaw Electronic Works: Wrocławskie Zakłady Elektroniczne „Elwro” 1959–2000 - Popiński, Krzysztof (Studia Historiae Oeconomicae, 2021)
Based on the research potential of the Wrocław higher education center and its achievements in mathematics and automation, Wrocławskie Zakłady Elektroniczne “Elwro” was launched in the capital of Lower Silesia, in the late 1950s. Starting with the production of relatively simple electrotechnical devices, the company transformed in just a few years into a manufacturer of digital machines of its own design, “Odra”. They have found wide application in science, administration, communication and industry − both in Poland and abroad, mainly in the Comecon member states. The 1970s were the period of the peak development of WZE “Elwro”, in which apart from devices of its own design, computers belonging to the so-called Uniform System of Digital Electronic Machines of Comecon countries, were also being produced. The effects of the economic crisis of the 1980s abruptly reduced the orders for computers produced in “Elwro”, and their development and production was slowed down by problems with obtaining materials that were scarce in the country and foreign currency for foreign purchases. The technological distance between the “Elwro” offer and the equipment manufactured in the leading countries of the West was growing. After the start of the system transformation in the country, the management of “Elwro” attempted to carry out radical organizational transformations and grant the company the status of a joint-stock company. However, they were held back for too long by both the lack of government support and the concerns of the works council. Meanwhile, deteriorating economic results forced the management of “Elwro” to reduce employment and sell more and more assets. Ultimately, in 1993, the plants were transformed into a sole-shareholder company of the State Treasury, and then sold to the German concern “Siemens”. For the new owner, the only thing that mattered was the access to the Polish telecommunications market obtained in this way. He did not use the still existing human resources and production potential of “Elwro” and, shortly after the purchase, practically liquidated the company. In 2000, its remains were sold to the American telecommunications company “Teletec Holding”, which changed the name of the company to “Teletec Polska” S.A.